Durable double-layer composite super-hydrophobic anti-icing coating and preparation method and application thereof
Patent Information
- Application Number
- CN202610945562.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-08-28
AI Technical Summary
[0005]本发明的目的在于提供一种耐久双层复合超疏水防冰涂层及其制备方法与应用,以解决或改善上述技术问题
本发明通过在基底表面依次构筑环氧树脂粘结层和复合功能层,制备得到具有低液滴黏附、长效抗结冰、自清洁和防污性能的双层超疏水防冰涂层。其中,环氧树脂粘结层用于增强涂层与基底之间的界面结合力,并对复合功能层中的无机微纳米颗粒产生包埋和锚定作用;复合功能层通过微纳米级别的金属元素X的氧化物颗粒与纳米级别的二氧化硅颗粒共同构筑微纳米层级粗糙结构,并利用聚二甲基硅氧烷形成低表面能硅氧烷界面,从而实现稳定的Cassie-Baxter润湿状态。
Smart Images

Figure CN122647982A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating materials technology, and more specifically, to a durable double-layer composite superhydrophobic anti-icing coating, its preparation method, and its application. Background Technology
[0002] Ice accumulation is widespread in transportation, energy facilities, power transmission lines, wind power generation, building exteriors, and cryogenic equipment. Ice formation not only increases structural loads and reduces equipment operating efficiency, but can also lead to mechanical failures, line damage, traffic accidents, and energy supply disruptions. Therefore, developing efficient, stable, low-energy-consumption anti-icing materials suitable for large-area engineering surfaces is of great significance.
[0003] In recent years, passive anti-icing technology based on surface engineering has received widespread attention. Among these, superhydrophobic surfaces, due to their high water contact angle, low roll-off angle, and low droplet adhesion characteristics, can reduce the residence time of water droplets on the surface and achieve anti-icing effects by reducing the actual solid-liquid contact area, trapping the interfacial air layer, and delaying the heterogeneous ice nucleation process. However, existing superhydrophobic anti-icing coatings still have some limitations: On the one hand, some superhydrophobic surfaces rely on methods such as laser etching, template replication, chemical vapor deposition, or fluorine-containing low surface energy modification for preparation, which suffer from complex processes, high equipment requirements, high costs, limited substrate adaptability, or insufficient environmental friendliness, hindering large-scale engineering applications. On the other hand, many particulate superhydrophobic coatings have insufficient adhesion between the coating and the substrate, making them prone to coating detachment and damage under water flow impact, sand impact, friction and wear, tape peeling, or acid / alkali environments, leading to a decline in superhydrophobic and anti-icing performance.
[0004] In view of this, the present invention is proposed. Summary of the Invention
[0005] The purpose of this invention is to provide a durable double-layer composite superhydrophobic anti-icing coating, its preparation method and application, in order to solve or improve the above-mentioned technical problems.
[0006] This invention can be implemented as follows: In a first aspect, the present invention provides a durable double-layer composite superhydrophobic anti-icing coating, the durable double-layer composite superhydrophobic anti-icing coating comprising an epoxy resin adhesive layer disposed on the surface of a substrate, and a composite functional layer disposed on the surface of the epoxy resin adhesive layer. The raw materials for preparing the epoxy resin adhesive layer include 3.5 to 4.5 parts epoxy resin, 1 part first curing agent, and 18 to 22 parts first organic solvent; The raw materials for preparing the composite functional layer include 10 parts of polydimethylsiloxane, 1 part of a second curing agent, inorganic micro / nano particles, and 300 to 400 parts of a second organic solvent; the inorganic micro / nano particles include 4 to 6 parts of nano-sized silica particles and 22 to 34 parts of micro / nano-sized oxide particles of metal element X, wherein element X includes at least one of Al and Ti.
[0007] In an optional embodiment, the epoxy resin includes at least one of E-44 epoxy resin and E-51 epoxy resin. And / or, the first curing agent includes at least one of polyetheramine D230 curing agent, polyamide 650 curing agent, and polyamide 651 curing agent; And / or, the first organic solvent includes at least one of ethyl acetate, ethanol, and acetone.
[0008] In an optional embodiment, the oxide particles of metal element X include 4 to 6 parts of first X oxide particles with a particle size of 30 nm, 4 to 6 parts of second X oxide particles with a particle size of 30 nm to 50 nm, 4 to 6 parts of third X oxide particles with a particle size of 0.2 μm, 4 to 6 parts of fourth X oxide particles with a particle size of 0.3 μm, and 6 to 10 parts of fifth X oxide particles with a particle size of 5 μm to 6 μm.
[0009] In an optional embodiment, the second curing agent includes DOWSIL SYLGARD 184 curing agent; And / or, the second organic solvent includes at least one of ethyl acetate, acetone, and ethanol; And / or, the particle size of the silica particles is 7nm~40nm.
[0010] In an optional embodiment, the durable dual-layer composite superhydrophobic anti-icing coating has at least one of the following characteristics: Feature 1: The static water contact angle of the durable double-layer composite superhydrophobic anti-icing coating is ≥160° and the roll-off angle is ≤1°; Feature 2: At -15℃, water droplets remain unfrozen for more than 1 hour on the surface of the durable double-layer composite superhydrophobic anti-icing coating.
[0011] Secondly, the present invention provides a method for preparing a durable double-layer composite superhydrophobic anti-icing coating as described in any of the foregoing embodiments, comprising the following steps: preparing an epoxy resin bonding layer on the surface of a substrate, preparing a composite functional layer on the surface of the epoxy resin bonding layer, and curing.
[0012] In an optional embodiment, the preparation of the epoxy resin adhesive layer includes: spraying a mixed solution of epoxy resin, a first curing agent and a first organic solvent onto the substrate surface; The spraying conditions include: a spraying angle of 40° to 50°, a spraying distance of 10cm to 20cm, and a spraying pressure of 0.3MPa to 0.5MPa.
[0013] In an optional embodiment, the preparation of the composite functional layer includes: spraying a mixed solution of polydimethylsiloxane, a second curing agent, inorganic micro-nano particles and a second organic solvent onto the surface of a semi-cured epoxy resin adhesive layer. The spraying conditions include: a spraying angle of 40° to 50°, a spraying distance of 10cm to 20cm, and a spraying pressure of 0.3MPa to 0.5MPa.
[0014] In an optional embodiment, the curing temperature is 60℃~100℃ and the curing time is 0.5h~2h.
[0015] Thirdly, the present invention provides an anti-icing product having a durable double-layer composite superhydrophobic anti-icing coating as described in any of the foregoing embodiments.
[0016] The beneficial effects of this invention include: This invention prepares a double-layer superhydrophobic anti-icing coating with low droplet adhesion, long-lasting anti-icing, self-cleaning, and antifouling properties by sequentially constructing an epoxy resin bonding layer and a composite functional layer on the substrate surface. The epoxy resin bonding layer enhances the interfacial adhesion between the coating and the substrate and embeds and anchors the inorganic micro / nano particles in the composite functional layer. The composite functional layer constructs a micro / nano-level rough structure through micro / nano-scale oxide particles of metal element X and nano-scale silica particles, and utilizes polydimethylsiloxane to form a low surface energy siloxane interface, thereby achieving a stable Cassie-Baxter wetting state.
[0017] Compared to conventional superhydrophobic anti-icing coatings, the durable dual-layer composite superhydrophobic anti-icing coating provided by this invention can significantly enhance the mechanical durability, chemical stability and long-term anti-icing performance of the coating while improving interfacial adhesion and particle stability.
[0018] In addition, the preparation process of this durable double-layer composite superhydrophobic anti-icing coating is simple, environmentally friendly, low-cost, and suitable for large-area spraying. It can be applied to the anti-icing protection of glass, concrete, metal, power transmission lines, wind turbine blades, transportation facilities, building exterior surfaces, and equipment in low-temperature service. Attached Figure Description
[0019] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1 The image shows the field emission scanning electron microscope result of the durable double-layer composite superhydrophobic anti-icing coating prepared in Example 1. Figure 2 The image shows the field emission scanning electron microscope result of the coating prepared in Comparative Example 2. Figure 3 An atomic force microscope image of the durable double-layer composite superhydrophobic anti-icing coating prepared in Example 1; Figure 4 An atomic force microscope image of the coating prepared in Comparative Example 2; Figure 5 The image shows the wetting performance of the durable double-layer composite superhydrophobic anti-icing coating prepared in Example 1. Figure 6 The image shows the wetting properties of the coating prepared in Comparative Example 2. Figure 7 The graph shows the freezing delay time results of the freezing process at -15°C for each embodiment and comparative example. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0022] The following is a detailed description of the durable double-layer composite superhydrophobic anti-icing coating, its preparation method, and its application provided by the present invention.
[0023] The present invention provides a durable double-layer composite superhydrophobic anti-icing coating, which includes an epoxy resin adhesive layer disposed on the surface of a substrate and a composite functional layer disposed on the surface of the epoxy resin adhesive layer.
[0024] [Base] In some alternative implementations, the substrate may, by way of example but not by way of limitation, include one of glass, metal and concrete, etc.
[0025] Epoxy resin adhesive layer The raw materials for preparing the epoxy resin adhesive layer include 3.5 to 4.5 parts epoxy resin, 1 part first curing agent, and 18 to 22 parts first organic solvent.
[0026] In some optional embodiments, the content of epoxy resin in the raw materials for preparing the epoxy resin adhesive layer can be 3.5 parts, 4 parts, or 4.5 parts, or other values within the range of 3.5 parts to 4.5 parts.
[0027] The content of the first organic solvent in the raw materials for preparing the epoxy resin adhesive layer can be 18 parts, 19 parts, 20 parts, 21 parts or 22 parts, or other values within the range of 18 parts to 22 parts.
[0028] In some preferred embodiments, the raw materials for preparing the epoxy resin adhesive layer include 4 parts epoxy resin, 1 part first curing agent and 20 parts first organic solvent.
[0029] In some alternative embodiments, the epoxy resin may exemplary include at least one of E-44 epoxy resin and E-51 epoxy resin.
[0030] The first curing agent may, by way of example, include at least one of polyetheramine D230 curing agent, polyamide 650 curing agent, and polyamide 651 curing agent.
[0031] The first organic solvent may, by way of example, include at least one of ethyl acetate, ethanol, and acetone.
[0032] In some alternative embodiments, the thickness of the epoxy resin adhesive layer can be 150nm to 250nm, such as 150nm, 200nm or 250nm, or other values within the range of 150nm to 250nm.
[0033] The epoxy resin adhesive layer mentioned above is mainly used to enhance the interfacial bonding force between the coating and the substrate, and to embed, anchor and mechanically lock the inorganic particles in the composite functional layer in the semi-cured state.
[0034]
Composite Functional Layer
[0035] In some optional embodiments, the content of inorganic micro / nano particles in the raw materials for preparing the composite functional layer can be 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, or 38 parts, or other values within the range of 26 parts to 38 parts. The content of silica particles can be 4 parts, 4.5 parts, 5 parts, 5.5 parts, or 6 parts, or other values within the range of 4 parts to 6 parts. The content of micro / nano-level oxide particles of metal element X can be 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, or 34 parts, or other values within the range of 22 parts to 34 parts.
[0036] In some preferred embodiments, the raw materials for preparing the composite functional layer include 10 parts polydimethylsiloxane, 1 part a second curing agent, 28 parts inorganic micro / nano particles, and 360 parts a second organic solvent. The 28 parts of inorganic micro / nano particles consist of 4 parts nano-sized silica particles and 24 parts micro / nano-sized oxide particles of metal element X.
[0037] In some alternative embodiments, the particle size of the silica particles can be 7nm to 40nm, such as 7nm, 10nm, 15nm, 20nm, 30nm or 40nm, or other values within the range of 7nm to 40nm.
[0038] In some optional embodiments, the oxide particles of metal element X include 4 to 6 parts of first X oxide particles with a particle size of 30 nm, 4 to 6 parts of second X oxide particles with a particle size of 30 nm to 50 nm, 4 to 6 parts of third X oxide particles with a particle size of 0.2 μm, 4 to 6 parts of fourth X oxide particles with a particle size of 0.3 μm, and 6 to 10 parts of fifth X oxide particles with a particle size of 5 μm to 6 μm.
[0039] The aforementioned first X oxide particles, second X oxide particles, third X oxide particles, fourth X oxide particles, and fifth X oxide particles are all oxide particles of metallic element X, differing only in particle size. Specifically, the first X oxide particles were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; the second X oxide particles were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; the third X oxide particles were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; the fourth X oxide particles were purchased from Guangdong Best Chemical Technology Co., Ltd.; and the fifth X oxide particles were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.
[0040] The content of the first, second, third, and fourth oxide particles can each independently be 4 parts, 4.5 parts, 5 parts, 5.5 parts, or 6 parts, or other values within the range of 4 to 6 parts. The content of the fifth oxide particle can be 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, or 10 parts, or other values within the range of 6 to 10 parts. In some preferred embodiments, the oxide particles of metal element X include 4 parts of the first oxide particle with a particle size of 30 nm, 4 parts of the second oxide particle with a particle size of 30 nm to 50 nm, 4 parts of the third oxide particle with a particle size of 0.2 μm, 4 parts of the fourth oxide particle with a particle size of 0.3 μm, and 8 parts of the fifth oxide particle with a particle size of 5 μm to 6 μm.
[0041] The content of the second organic solvent in the raw materials for preparing the composite functional layer can be 300 parts, 310 parts, 320 parts, 330 parts, 340 parts, 350 parts, 360 parts, 370 parts, 380 parts, 390 parts or 400 parts, or other values in the range of 300 parts to 400 parts.
[0042] In some alternative embodiments, the second curing agent may exemplary include DOWSIL SYLGARD 184 curing agent.
[0043] The second organic solvent may, by way of example, include at least one of ethyl acetate, acetone, and ethanol.
[0044] In some alternative implementations, the thickness of the composite functional layer can be 150nm to 250nm, such as 150nm, 200nm or 250nm, or other values within the range of 150nm to 250nm.
[0045] The aforementioned composite functional layer constructs a micro-nano hierarchical rough structure through the co-construction of micro-nano-scale oxide particles of metal element X and nano-scale silica particles. Specifically, the micro-nano-scale oxide particles of metal element X are used to construct a micrometer- or sub-micrometer-scale hard rough framework, while the nano-scale silica particles are used to construct a nano-scale secondary rough structure. Polydimethylsiloxane, as a low surface energy component, coats the inorganic micro-nano particles and forms a siloxane network during the curing process. On one hand, polydimethylsiloxane can reduce the surface free energy of the coating, resulting in water droplets exhibiting a high contact angle and a low roll-off angle on the coating surface; on the other hand, polydimethylsiloxane can act as a flexible binder phase to fix the inorganic particles, improving the stability of the rough structure under external impact, friction, and peeling. By coating inorganic particles with polydimethylsiloxane and forming a low surface energy siloxane interface, air can be trapped between water droplets and the coating surface, stabilizing the Cassie-Baxter wetting state, reducing the actual solid-liquid contact area, reducing the exposure of solid nucleation sites, and inhibiting the stable formation of critical ice nuclei through the interfacial air layer and micro-nano confinement structure, thereby increasing the heterogeneous ice nucleation energy barrier, achieving long-term freezing delay, and improving anti-icing performance.
[0046]
Durable Dual-Layer Composite Superhydrophobic Anti-icing Coating
[0047] In some alternative implementations, water droplets remain unfrozen for more than 1 hour on the surface of the durable double-layer composite superhydrophobic anti-icing coating at -15°C, which means that the freezing of water droplets can be significantly delayed in low-temperature environments.
[0048] Furthermore, the durable dual-layer composite superhydrophobic anti-icing coating maintains excellent superhydrophobic properties even after water flow impact, sand particle impact, sandpaper abrasion, tape peeling, and acid / alkali immersion. Compared to traditional particulate superhydrophobic anti-icing coatings, the durable dual-layer composite superhydrophobic anti-icing coating of this invention can significantly enhance the coating's mechanical durability, chemical stability, and long-term anti-icing performance while improving interfacial adhesion and particle stability.
[0049] Accordingly, the present invention also provides a method for preparing the above-mentioned durable double-layer composite superhydrophobic anti-icing coating, comprising the following steps: preparing an epoxy resin bonding layer on the surface of a substrate, preparing a composite functional layer on the surface of the epoxy resin bonding layer, and curing.
[0050] In some alternative embodiments, the substrate can be pretreated before preparing the epoxy resin adhesive layer. Cleaning and drying the substrate surface can remove surface oil, dust, and impurities, improving the bonding stability between the coating and the substrate. For example, the substrate can be ultrasonically cleaned sequentially in ethanol and deionized water, and then air-dried at room temperature for later use.
[0051] In some alternative embodiments, the preparation of the epoxy resin adhesive layer may include spraying a mixed solution of epoxy resin, a first curing agent and a first organic solvent onto the substrate surface.
[0052] The spraying conditions include: the spraying angle can be 40°~50°, such as 40°, 42°, 45°, 48° or 50°, or other values within the range of 40°~50°.
[0053] The spraying distance can be 10cm to 20cm, such as 10cm, 12cm, 15cm, 18cm or 20cm, or other values within the range of 10cm to 20cm.
[0054] The spraying pressure can be 0.3MPa~0.5MPa, such as 0.3MPa, 0.35MPa, 0.4MPa, 0.45MPa or 0.5MPa, or other values within the range of 0.3MPa~0.5MPa.
[0055] It should be noted that, in this invention, before preparing the composite functional layer, the epoxy resin adhesive layer formed by spraying needs to be left to stand so that it is in a semi-cured state with a certain degree of adhesion, so as to facilitate the embedding and fixation of inorganic particles in the subsequent composite functional layer, forming a particle embedding and mechanical interlocking interface, and avoiding problems such as easy particle detachment, insufficient coating adhesion and poor wear resistance.
[0056] In some alternative embodiments, the preparation of the composite functional layer may include spraying a mixed solution of polydimethylsiloxane, a second curing agent, inorganic micro / nano particles and a second organic solvent onto the surface of a semi-cured epoxy resin adhesive layer.
[0057] The spraying conditions include: the spraying angle can be 40°~50°, such as 40°, 42°, 45°, 48° or 50°, or other values within the range of 40°~50°.
[0058] The spraying distance can be 10cm to 20cm, such as 10cm, 12cm, 15cm, 18cm or 20cm, or other values within the range of 10cm to 20cm.
[0059] The spraying pressure can be 0.3MPa~0.5MPa, such as 0.3MPa, 0.35MPa, 0.4MPa, 0.45MPa or 0.5MPa, or other values within the range of 0.3MPa~0.5MPa.
[0060] In some alternative embodiments, the curing temperature can be 60℃~100℃, such as 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃ or 100℃, or other values within the range of 60℃~100℃.
[0061] The curing time can be 0.5h to 2h, such as 0.5h, 1h, 1.5h or 2h, or other values within the range of 0.5h to 2h.
[0062] In addition, the present invention also provides an anti-icing product having the above-mentioned durable double-layer composite superhydrophobic anti-icing coating.
[0063] In some alternative implementations, anti-icing products may, by way of example but not by way of limitation, include glass, concrete, metal, power transmission lines, wind turbine blades, transportation facilities, building exteriors, and cryogenic equipment.
[0064] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0065] In the following examples and comparative examples, the silica particles with a diameter of 20 nm were purchased from Shanghai Maclean Biochemical Technology Co., Ltd. (A741990-100); the alumina particles with a diameter of 20 nm were purchased from Shanghai Maclean Biochemical Technology Co., Ltd. (N817513-100g); the alumina particles with a diameter of 30 nm were purchased from Shanghai Maclean Biochemical Technology Co., Ltd. (A801481-25g); the alumina particles with a diameter of 30 nm to 50 nm were purchased from Shanghai Maclean Biochemical Technology Co., Ltd. (A874524-25g); the alumina particles with a diameter of 0.2 μm were purchased from Shanghai Maclean Biochemical Technology Co., Ltd. (A810836-100g); the alumina particles with a diameter of 0.3 μm were purchased from Guangdong Best Chemical Technology Co., Ltd.; and the alumina particles with a diameter of 5 μm to 6 μm were purchased from Shanghai Maclean Biochemical Technology Co., Ltd. (A800195-25g). Titanium dioxide particles with a diameter of 30 nm were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; titanium dioxide particles with a diameter of 30 nm to 50 nm were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; titanium dioxide particles with a diameter of 0.2 μm were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; titanium dioxide particles with a diameter of 0.3 μm were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; and titanium dioxide particles with a diameter of 5 μm to 6 μm were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.
[0066] Example 1 This embodiment provides a dual-layer composite superhydrophobic anti-icing coating, including an epoxy resin adhesive layer disposed on the surface of a substrate, and a composite functional layer disposed on the surface of the epoxy resin adhesive layer.
[0067] The substrate is glass.
[0068] The raw materials for preparing the epoxy resin adhesive layer include: 4 parts E-44 epoxy resin, 1 part polyetheramine D230 epoxy resin curing agent, and 20 parts ethyl acetate; The raw materials for preparing the composite functional layer include: 10 parts polydimethylsiloxane, 1 part DOWSIL SYLGARD 184 curing agent, 28 parts inorganic micro / nano particles, and 360 parts ethyl acetate. The 28 parts of inorganic micro / nano particles consist of 4 parts silica particles with a diameter of 20 nm, 4 parts alumina particles with a diameter of 30 nm, 4 parts alumina particles with a diameter of 30 nm–50 nm, 4 parts alumina particles with a diameter of 0.2 μm, 4 parts alumina particles with a diameter of 0.3 μm, and 8 parts alumina particles with a diameter of 5 μm–6 μm.
[0069] The preparation method of the above-mentioned durable double-layer composite superhydrophobic anti-icing coating includes the following steps: S1: Substrate pretreatment.
[0070] The substrate was ultrasonically cleaned in ethanol and deionized water in sequence, for 5 minutes in each cleaning solution, and then air-dried at room temperature for later use.
[0071] S2: Prepare the epoxy resin adhesive layer.
[0072] According to the above composition and proportion, the raw materials for preparing the epoxy resin adhesive layer were magnetically stirred at room temperature for 20 minutes, and then sprayed onto the substrate surface using a spray gun at a spraying angle of 45°, a spraying distance of 20cm and a spraying pressure of 0.4MPa.
[0073] S3: Let it stand still.
[0074] The substrate coated with the epoxy resin adhesive layer was left to stand at room temperature for 15 minutes to allow the epoxy resin adhesive layer to be in a semi-cured state with adhesive properties.
[0075] S4: Prepare and spray the composite functional layer.
[0076] According to the above composition and ratio, the raw materials for preparing the composite functional layer were magnetically stirred at room temperature for 30 minutes and then ultrasonically dispersed for 20 minutes to obtain a uniform and stable suspension. Subsequently, the suspension was sprayed onto the surface of the epoxy resin adhesive layer with a spray gun at a spray angle of 45°, a spray distance of 20cm and a spray pressure of 0.4MPa.
[0077] S5: Curing treatment.
[0078] The sample obtained in S4 was cured in an oven at 80°C for 1 hour, and then left to stand at room temperature for 12 hours.
[0079] Example 2 The difference between this embodiment and Embodiment 1 is that the alumina particles are replaced with titanium dioxide particles of the same size.
[0080] Example 3 This embodiment provides a dual-layer composite superhydrophobic anti-icing coating, including an epoxy resin adhesive layer disposed on the surface of a substrate, and a composite functional layer disposed on the surface of the epoxy resin adhesive layer.
[0081] The substrate is glass.
[0082] The raw materials for preparing the epoxy resin adhesive layer include: 3.5 parts E-44 epoxy resin, 1 part polyamide 650 curing agent, and 18 parts ethanol; The raw materials for preparing the composite functional layer include: 10 parts polydimethylsiloxane, 1 part DOWSIL SYLGARD 184 curing agent, 31 parts inorganic micro / nano particles, and 300 parts ethanol. The 31 parts of inorganic micro / nano particles consist of 5 parts silica particles with a particle size of 7 nm, 5 parts alumina particles with a particle size of 30 nm, 5 parts alumina particles with a particle size of 30 nm–50 nm, 5 parts alumina particles with a particle size of 0.2 μm, 5 parts alumina particles with a particle size of 0.3 μm, and 6 parts alumina particles with a particle size of 5 μm–6 μm.
[0083] The preparation method of the above-mentioned durable double-layer composite superhydrophobic anti-icing coating includes the following steps: S1: Substrate pretreatment.
[0084] The substrate was ultrasonically cleaned in ethanol and deionized water in sequence, for 5 minutes in each cleaning solution, and then air-dried at room temperature for later use.
[0085] S2: Prepare the epoxy resin adhesive layer.
[0086] According to the above composition and ratio, the raw materials for preparing the epoxy resin adhesive layer were magnetically stirred at room temperature for 20 minutes, and then sprayed onto the substrate surface using a spray gun at a spraying angle of 40°, a spraying distance of 10cm and a spraying pressure of 0.3MPa.
[0087] S3: Let it stand still.
[0088] The substrate coated with the epoxy resin adhesive layer was left to stand at room temperature for 15 minutes to allow the epoxy resin adhesive layer to be in a semi-cured state with adhesive properties.
[0089] S4: Prepare and spray the composite functional layer.
[0090] According to the above composition and ratio, the raw materials for preparing the composite functional layer were magnetically stirred at room temperature for 30 minutes and then ultrasonically dispersed for 20 minutes to obtain a uniform and stable suspension. Subsequently, the suspension was sprayed onto the surface of the epoxy resin adhesive layer with a spray gun at a spray angle of 40°, a spray distance of 10cm and a spray pressure of 0.3MPa.
[0091] S5: Curing treatment.
[0092] The sample obtained in S4 was cured in an oven at 60°C for 2 hours, and then left to stand at room temperature for 12 hours.
[0093] Example 4 This embodiment provides a dual-layer composite superhydrophobic anti-icing coating, including an epoxy resin adhesive layer disposed on the surface of a substrate, and a composite functional layer disposed on the surface of the epoxy resin adhesive layer.
[0094] The base is made of concrete.
[0095] The raw materials for preparing the epoxy resin adhesive layer include: 4.5 parts E-51 epoxy resin, 1 part polyamide 651 curing agent, and 22 parts ethanol; The raw materials for preparing the composite functional layer include: 10 parts polydimethylsiloxane, 1 part DOWSIL SYLGARD 184 curing agent, 40 parts inorganic micro / nano particles, and 400 parts ethanol. The 40 parts of inorganic micro / nano particles consist of 6 parts silica particles with a particle size of 40 nm, 6 parts alumina particles with a particle size of 30 nm, 6 parts alumina particles with a particle size of 30 nm–50 nm, 6 parts alumina particles with a particle size of 0.2 μm, 6 parts alumina particles with a particle size of 0.3 μm, and 10 parts alumina particles with a particle size of 5 μm–6 μm.
[0096] The preparation method of the above-mentioned durable double-layer composite superhydrophobic anti-icing coating includes the following steps: S1: Substrate pretreatment.
[0097] The substrate was ultrasonically cleaned in ethanol and deionized water in sequence, for 5 minutes in each cleaning solution, and then air-dried at room temperature for later use.
[0098] S2: Prepare the epoxy resin adhesive layer.
[0099] According to the above composition and ratio, the raw materials for preparing the epoxy resin adhesive layer were magnetically stirred at room temperature for 20 minutes, and then sprayed onto the substrate surface using a spray gun at a spraying angle of 50°, a spraying distance of 20cm and a spraying pressure of 0.5MPa.
[0100] S3: Let it stand still.
[0101] The substrate coated with the epoxy resin adhesive layer was left to stand at room temperature for 15 minutes to allow the epoxy resin adhesive layer to be in a semi-cured state with adhesive properties.
[0102] S4: Prepare and spray the composite functional layer.
[0103] According to the above composition and ratio, the raw materials for preparing the composite functional layer were magnetically stirred at room temperature for 30 minutes and then ultrasonically dispersed for 20 minutes to obtain a uniform and stable suspension. Subsequently, the suspension was sprayed onto the surface of the epoxy resin adhesive layer with a spray gun at a spray angle of 50°, a spray distance of 20cm and a spray pressure of 0.5MPa.
[0104] S5: Curing treatment.
[0105] The sample obtained in S4 was cured in an oven at 100°C for 0.5 h, and then left to stand at room temperature for 12 h.
[0106] Comparative Example 1 The difference between this comparative example and Example 1 is that there is no epoxy resin adhesive layer, and the composite functional layer is prepared directly on the substrate surface.
[0107] Comparative Example 2 The difference between this comparative example and Example 1 is that the silica particles with a particle size of 20 nm in the composite functional layer are replaced with alumina particles with a particle size of 20 nm.
[0108] Comparative Example 3 The difference between this comparative example and Example 1 is that the standing treatment in S3 was not performed.
[0109] Test case The coatings prepared in Examples 1-2 and Comparative Examples 1-3 were subjected to the following tests.
[0110] (1) Surface morphology and chemical element analysis Taking Example 1 and Comparative Example 2 as examples, the prepared durable bilayer composite superhydrophobic anti-icing coating was observed by field emission scanning electron microscopy and atomic force microscopy. The field emission scanning electron microscopy results are as follows: Figure 1 and Figure 2 As shown, the atomic force microscopy observation results are as follows: Figure 3 and Figure 4 As shown.
[0111] according to Figure 1 It can be seen that the surface of the bilayer composite superhydrophobic coating prepared in Example 1 has obvious micro-nano secondary roughness structure, which is the key to the coating's superhydrophobic properties. Through comparison... Figure 1 and Figure 2It can be seen that Example 1 with added nano-silica has more structural voids and less particle aggregation than Comparative Example 2 without added nano-silica.
[0112] according to Figure 3 and Figure 4 It can be seen that the roughness of Example 1 is significantly higher than that of Example 2, indicating that the coating with added silica has more nanopores, which can accommodate more air and thus obtain a higher contact angle and a lower roll-off angle, resulting in a longer freezing delay time.
[0113] (2) Wetting performance test Taking Example 1 and Comparative Example 2 as examples, the surface wettability of the prepared durable double-layer composite superhydrophobic anti-icing coating was tested using a contact angle meter (SDC-100S, China). The test results are as follows: Figure 5 and Figure 6 As shown in Table 1, the test data is as follows.
[0114] (3) Durability test The mechanical durability of the coatings prepared in some examples and comparative examples was systematically evaluated using water droplet impact (ASTM G73-21), abrasive impact (GB / T 18658-2018), sandpaper abrasion (GB / T45017-2024), and tape peel test (GB / T 45017-2024). The chemical stability of the coatings prepared in some examples and comparative examples was examined using an acid / alkali solution immersion test (ASTM D6943-15(2024)). During the tests, the evolution of the water contact angle (CA) and roll-off angle (SA) was used as the main evaluation criteria to characterize the coatings' ability to maintain a low-adhesion superhydrophobic state under various mechanical and chemical influences. The test results are shown in Table 1.
[0115] (4) Anti-icing performance test The anti-icing performance of the coatings prepared in each embodiment and comparative example was tested in a high and low temperature test chamber at temperatures of -15℃ and -20℃, with relative humidity controlled at approximately 40%. The freezing process of 10μL water droplets on different surfaces was recorded in real time using a high-speed camera. The results are shown in Table 1 and [Table data missing]. Figure 7 As shown, where, Figure 7 The freezing delay time for each embodiment and comparative example during the freezing process at -15°C.
[0116] (5) Self-cleaning and anti-fouling performance test The self-cleaning ability of the coatings prepared in each embodiment and comparative example was evaluated. Specifically, quartz sand was used as a solid contaminant to simulate the adhesion of dust and particulate contaminants to the coating surface in an outdoor environment. During the test, the sample was placed in a petri dish at a 30° tilt angle, and then quartz sand was randomly dispersed on the sample surface. Deionized water was then rolled down the surface using a dropper, and the contaminant removal process was recorded with a camera. The contact angle of different colored contaminant liquids was measured on the sample surface to evaluate the antifouling performance. The results are shown in Table 1.
[0117] Table 1 Test Results
[0118] As shown in Table 1, the initial water contact angle of the double-layer composite superhydrophobic anti-icing coating obtained in Example 1 is 163.4°, and the roll-off angle is 0.4°, exhibiting excellent superhydrophobic properties. After being subjected to 5L water impact, 500g abrasive impact, 50 grinding cycles, and 50 tape peeling cycles, its water contact angle still remained above 152.7°, and the roll-off angle was no higher than 6.5°, indicating that the coating has good mechanical durability and interfacial bonding stability.
[0119] In Example 2, after replacing the alumina particles in Example 1 with titanium dioxide particles of the same particle size, the coating still exhibited a water contact angle of 162.3° and a roll-off angle of 0.5°. Furthermore, after the aforementioned durability tests, it largely maintained its superhydrophobic properties, indicating that titanium dioxide particles can also effectively construct a multi-scale rough structure in conjunction with polydimethylsiloxane and nano-silica. Regarding anti-icing performance, Example 2 achieved freezing times of ≥2865s and 899s at -15℃ and -20℃, respectively, significantly superior to the comparative examples, demonstrating its good freezing delay capability.
[0120] As can be seen from Examples 1 and 2, when the oxide particles of the micro-nano-level metal element X are alumina particles, the resulting coating exhibits better mechanical durability and anti-icing performance.
[0121] Compared with Example 1, Comparative Example 1 did not have an epoxy resin adhesive layer. Although its initial contact angle reached 160.1°, after 50 grinding cycles and 50 tape peeling cycles, the contact angle decreased to 138.4° and 135.8°, respectively, and the roll-off angle increased to 25.2° and 22.5°, respectively. This shows that the epoxy resin adhesive layer can significantly enhance the bonding force between the functional layer and the substrate and improve the coating durability.
[0122] Compared with Example 1, in Comparative Example 2, after replacing 20nm SiO2 with Al2O3 of the same particle size, the coating roll-off angle increased to 0.8° and the freezing time at -15℃ decreased to 1436s, indicating that nano-SiO2 plays an important role in constructing low-adhesion micro-nano structures and improving anti-icing performance.
[0123] Compared with Example 1, in Comparative Example 3, the adhesive layer was not allowed to stand to a semi-cured state before the functional layer was sprayed. The contact angle of the resulting coating was reduced to 151.9° and the freezing time at -15°C was only 751s. This shows that the surface condition of the bottom adhesive layer and the timing of spraying have a significant impact on interlayer bonding and final performance.
[0124] Furthermore, in Example 1, the freezing times at -15℃ and -20℃ reached ≥3763s and 1145s, respectively, and the ice nucleation temperature decreased to -26.3℃, both superior to the comparative example. This indicates that the bilayer composite superhydrophobic anti-icing coating prepared by this invention can effectively delay water droplet freezing and reduce the tendency for ice nucleation. Combined with... Figure 7 Examples 1 and 2 did not freeze within the observation time, while Comparative Examples 1-3 showed freezing phenomena at 2162s, 1436s, and 751s, indicating that Examples 1 and 2, with their obvious micro / nano structures, exhibited durable freeze-delay performance. Comparative Example 1, lacking epoxy resin bonding, experienced a change in its bottom bonding state during freezing, thus weakening its anti-icing performance. Comparative Example 2, by replacing silica with alumina particles, significantly weakened its micro / nano structure, thereby reducing its anti-icing performance. Comparative Example 3, because it was sprayed while the epoxy resin was still liquid, resulted in most of the micro / nano structure being integrated into the epoxy resin and encapsulated, failing to form a complete micro / nano structure, greatly reducing its anti-icing performance.
[0125] Furthermore, the durable double-layer composite superhydrophobic anti-icing coatings prepared in Examples 3 and 4 were also subjected to the above-mentioned wetting and antifreezing performance tests. The results showed that the static water contact angle of the durable double-layer composite superhydrophobic anti-icing coatings prepared in these two examples was ≥160° and the roll-off angle was ≤1°. At -15°C, water droplets remained on the surface of the durable double-layer composite superhydrophobic anti-icing coating for more than 1 hour without freezing.
[0126] In summary, the solution provided by this invention has at least the following advantages compared to the prior art: (1) The durable double-layer composite superhydrophobic anti-icing coating provided by the present invention has a double-layer structure. The epoxy resin bonding layer can enhance the adhesion between the coating and the substrate, and in the semi-cured state, it can embed, anchor and mechanically lock the silica and alumina particles in the composite functional layer, thereby improving the problem of easy particle detachment and insufficient interfacial bonding in traditional particulate superhydrophobic coatings, and improving the interfacial stability between the coating and the substrate.
[0127] (2) The durable double-layer composite superhydrophobic anti-icing coating provided by the present invention constructs a micro-nano-level rough structure through silica and alumina and / or titanium dioxide particles. Among them, alumina and / or titanium dioxide particles provide a hard micron and / or submicron rough framework, and silica nanoparticles further construct a fine-scale secondary nanostructure, so that the coating surface forms a stable multi-scale rough morphology, which is beneficial for trapping air and reducing the actual solid-liquid contact area. In addition, the polydimethylsiloxane in the composite functional layer can form a low surface energy interface, which can coat inorganic particles and form a low surface energy siloxane network during the curing process, so that water droplets maintain a high contact angle and a low roll-off angle on the coating surface, achieving low droplet adhesion and rapid roll-off.
[0128] (3) The durable double-layer composite superhydrophobic anti-icing coating provided by the present invention has excellent superhydrophobic properties. The surface of the coating can form a stable Cassie-Baxter wetting state, the static water contact angle can reach more than 160°, and the roll-off angle can be as low as less than 1°, showing good water droplet repulsion ability.
[0129] (4) The durable double-layer composite superhydrophobic anti-icing coating provided by the present invention has good anti-icing performance. The surface of the coating has a low solid-liquid contact area, a stable interfacial air layer and a micro-nano confinement structure, which can effectively reduce the exposure of solid nucleation sites and inhibit the stable formation of critical ice nuclei, thereby increasing the nucleation energy barrier of heterogeneous ice and significantly delaying the freezing of water droplets. At -15°C, water droplets can remain unfrozen on its surface for more than 1 hour; at -20°C, its freezing delay time is significantly extended by about 13 times.
[0130] (5) The durable double-layer composite superhydrophobic anti-icing coating provided by the present invention has good mechanical and chemical durability. The coating can still maintain good superhydrophobic properties after water flow impact, sand impact, sandpaper abrasion, tape peeling and acid / alkali immersion, indicating that its micro-nano hierarchical structure and low surface energy interface have good stability.
[0131] (6) The method for preparing the durable double-layer composite superhydrophobic anti-icing coating provided by this invention is simple, low-cost, and suitable for large-area construction. This method does not rely on complex processes such as laser etching, template replication, chemical vapor deposition, or fluorine-containing modification. The coating can be prepared simply by conventional spraying and curing, and has good potential for engineering scale-up. In addition, the coating is prepared by combining organic and inorganic materials. The superhydrophobic properties can be achieved without adding any fluorides for surface modification, making it green and environmentally friendly.
[0132] (7) The durable double-layer composite superhydrophobic anti-icing coating provided by the present invention has good multi-substrate adaptability and application prospects. The coating can form a stable superhydrophobic layer on different substrate surfaces such as glass, concrete, and metal, and exhibits self-cleaning, antifouling and anti-icing properties. It is suitable for transportation facilities, power transmission lines, wind turbine blades, building exterior surfaces and low-temperature service equipment.
[0133] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A durable double-layer composite superhydrophobic anti-icing coating, characterized in that, The durable dual-layer composite superhydrophobic anti-icing coating includes an epoxy resin adhesive layer disposed on the surface of the substrate, and a composite functional layer disposed on the surface of the epoxy resin adhesive layer. The raw materials for preparing the epoxy resin adhesive layer include 3.5 to 4.5 parts epoxy resin, 1 part first curing agent, and 18 to 22 parts first organic solvent; The raw materials for preparing the composite functional layer include 10 parts of polydimethylsiloxane, 1 part of a second curing agent, inorganic micro / nano particles, and 300 to 400 parts of a second organic solvent; the inorganic micro / nano particles include 4 to 6 parts of nano-sized silica particles and 22 to 34 parts of micro / nano-sized oxide particles of metal element X, wherein element X includes at least one of Al and Ti.
2. The durable double-layer composite superhydrophobic anti-icing coating according to claim 1, characterized in that, The epoxy resin includes at least one of E-44 epoxy resin and E-51 epoxy resin; And / or, the first curing agent includes at least one of polyetheramine D230 curing agent, polyamide 650 curing agent, and polyamide 651 curing agent; And / or, the first organic solvent includes at least one of ethyl acetate, ethanol, and acetone.
3. The durable double-layer composite superhydrophobic anti-icing coating according to claim 1, characterized in that, The oxide particles of the metal element X include 4 to 6 parts of first X oxide particles with a particle size of 30 nm, 4 to 6 parts of second X oxide particles with a particle size of 30 nm to 50 nm, 4 to 6 parts of third X oxide particles with a particle size of 0.2 μm, 4 to 6 parts of fourth X oxide particles with a particle size of 0.3 μm, and 6 to 10 parts of fifth X oxide particles with a particle size of 5 μm to 6 μm.
4. The durable double-layer composite superhydrophobic anti-icing coating according to claim 1, characterized in that, The second curing agent includes DOWSIL SYLGARD 184 curing agent; And / or, the second organic solvent includes at least one of ethyl acetate, acetone, and ethanol; And / or, the particle size of the silica particles is 7nm~40nm.
5. The durable double-layer composite superhydrophobic anti-icing coating according to any one of claims 1 to 4, characterized in that, The durable dual-layer composite superhydrophobic anti-icing coating has at least one of the following characteristics: Feature 1: The static water contact angle of the durable double-layer composite superhydrophobic anti-icing coating is ≥160°, and the roll-off angle is ≤1°; Feature 2: At -15°C, water droplets remain unfrozen for more than 1 hour on the surface of the durable double-layer composite superhydrophobic anti-icing coating.
6. A method for preparing a durable double-layer composite superhydrophobic anti-icing coating as described in any one of claims 1 to 5, characterized in that, The process includes the following steps: preparing the epoxy resin adhesive layer on the substrate surface, preparing the composite functional layer on the surface of the epoxy resin adhesive layer, and curing.
7. The preparation method according to claim 6, characterized in that, The preparation of the epoxy resin adhesive layer includes: spraying a mixed solution of the epoxy resin, the first curing agent and the first organic solvent onto the surface of the substrate; The spraying conditions include: a spraying angle of 40° to 50°, a spraying distance of 10cm to 20cm, and a spraying pressure of 0.3MPa to 0.5MPa.
8. The preparation method according to claim 6, characterized in that, The preparation of the composite functional layer includes: spraying a mixed solution of the polydimethylsiloxane, the second curing agent, the inorganic micro-nano particles and the second organic solvent onto the surface of the epoxy resin adhesive layer in a semi-cured state; The spraying conditions include: a spraying angle of 40° to 50°, a spraying distance of 10cm to 20cm, and a spraying pressure of 0.3MPa to 0.5MPa.
9. The preparation method according to claim 6, characterized in that, The curing temperature is 60℃~100℃, and the curing time is 0.5h~2h.
10. An anti-icing product, characterized in that, The anti-icing product has a durable double-layer composite superhydrophobic anti-icing coating as described in any one of claims 1 to 6.